Building as storyteller, layered narratives in a Karoo art town - Pasch, Suzanne (My University, 2018)
The tranquil Karoo church town of Nieu-Bethesda is filled with stories of a rich heritage which traces back to fossils from 2 billion years ago, to when the continents were one, to the Khoisan and Boer living on the foothills of the Kompasberge and to renowned, mysterious ‘outsider’ artist Helen Martins’s world of concrete and stained glass sculptures. The significance of the town lies in the layers of these narratives. Through the proposed interventions these stories will be told. Today, art and tourism is central to the town’s existence and identity. The small town scale architectural intervention acts as the new front door, the threshold, to a Nieu-Bethesda town museum and visitor’s exploration platform. It provides an introduction, a starting point from which the town can be discovered, and offers a guiding presence through its exploration. Die Sprokie Skrywer serves to document, preserve and celebrate the art town’s narratives and unique heritage through architecture while crossing the paths, programmes and learning opportunities of locals with those of tourists. Focussed primarily on the fascinating Helen Martins story, this study and proposed intervention also revisits the existing Helen Martins Museum. It complements the place with a new concrete and glass art hub that leads visitors to experience the ‘Owl House’ as well as a new sculpture restoration facility with specialised concrete and glass art studios. It takes guidance in technique and materiality from the knowledge passed down by Helen Martins herself and from the seemingly magical contents and characters which she brought into being. These sculptures stand today, arranged as she left them, at the ‘Owl House’ where she lived, worked and philosophised. Here the local creatives of the town will finally have access to much needed spaces and equipment to pursue their artistic careers and practice these art forms in the spirit of the town’s history. “This is my World”, Helen Martins used to say. This thesis steps into the ‘outsider’ artist’s creative mind to explore her “world” of biblical, mythical, spiritual and artistic healing. Visitors and artists who wish to learn about this specialised field become integral to the proposed program. The new intervention introduces a space for healing and creative development through Martins’ unique artistic techniques as a way of empowering the predominantly Afrikaans speaking, Coloured community challenged by poverty and alcoholism. The facilities merge the daily programmes of locals, artists, children and visitors through the business and practice of art. Architecturally, the town’s rich existing urban fabric and the Owl House’s unique spatial, material and atmospheric experiences served as a design tool palette. Traditional, vernacular Nieu-Bethesda building methods and materials inspired a restrained intervention, contributing to the identity of the town. To be the Storyteller the architecture must merge historical context to functional spaces while simultaneously offering a new, interactive model for tourism. It becomes a character in the story, sensitively acting as this small town’s guide who reveals and remembers, enhancing experience and understanding.
This document is submitted in partial fulfillment for the degree: Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, 2018
Keywords: Artists--South Africa; Nieu-Bethesda (South Africa)